Prehospital Trauma Airway Management: An NAEMSP Position Statement and Resource Document. (4th January 2022) - Braithwaite, Sabina; Stephens, Christopher; Remick, Kyle; Barrett, Whitney; Guyette, Francis X.; Levy, Michael; Colwell, Christopher
Abstract: Definitive management of trauma is not possible in the out-of-hospital environment. Rapid treatment and transport of trauma casualties to a trauma center are vital to improve survival and outcomes. Prioritization and management of airway, oxygenation, ventilation, protection from gross aspiration, and physiologic optimization must be balanced against timely patient delivery to definitive care. The optimal prehospital airway management strategy for trauma has not been clearly defined; the best choice should be patient-specific. NAEMSP recommends: The approach to airway management and the choice of airway interventions in a trauma patient requires an iterative, individualized assessment that considers patient, clinician, and environmental factors. Optimal trauma airway management should focus on meeting the goals of adequate oxygenation and ventilation rather than on specific interventions. Emergency medical services (EMS) clinicians should perform frequent reassessments to determine if there is a need to escalate from basic to advanced airway interventions. Management of immediately life-threatening injuries should take priority over advanced airway insertion. Drug-assisted airway management should be considered within a comprehensive algorithm incorporating failed airway options and balanced management of pain, agitation, and delirium. EMS medical directors must be highly engaged in assuring clinician competence in trauma airway assessment, management, and interventions.